The Significance Of Universities In Enhancing Business For Students - Khayatovich, Niyazov Mirshod (Indonesian Journal Publisher, 2025)
This article explores the pivotal role of universities in fostering business acumen among students and preparing them for the challenges of the modern economy. It highlights the historical evolution of universities as centers of knowledge and innovation, tracing their impact on business education from ancient times to the digital age. The paper underscores how universities today serve as incubators for entrepreneurship, offering resources such as mentorship, capital, and experiential learning opportunities.